2022
DOI: 10.1038/s41598-022-16206-2
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus surface texture is associated with degenerative changes in biological and biomechanical properties

Abstract: Meniscal degeneration is defined by semi-quantitative assessment of multiple histological findings and has been implicated in biomechanical dysfunction, yet little is known about its relationship with biological properties. This paper aimed to quantitatively evaluate degenerative findings in human meniscus to examine their relationship with gene expression and biomechanical properties, and to extract histological findings that reflect biological properties like gene expression and cytokine secretion. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Meniscus degeneration, however, is a multi-faceted process that encompasses not just geometric alterations to the microstructure, but also changes in the biochemical composition, material properties, and structural organisation of the meniscus. Understanding meniscus degeneration will therefore ultimately require a holistic approach that goes beyond morphological alterations [29, 30]. As a first step, we here focus on the effect of microstructure geometry on fluid mechanics in the meniscus, which our computational model enables us to study in isolation.…”
Section: Resultsmentioning
confidence: 99%
“…Meniscus degeneration, however, is a multi-faceted process that encompasses not just geometric alterations to the microstructure, but also changes in the biochemical composition, material properties, and structural organisation of the meniscus. Understanding meniscus degeneration will therefore ultimately require a holistic approach that goes beyond morphological alterations [29, 30]. As a first step, we here focus on the effect of microstructure geometry on fluid mechanics in the meniscus, which our computational model enables us to study in isolation.…”
Section: Resultsmentioning
confidence: 99%
“…Although the impact of inflammation has been extensively documented to contribute to the progressive decay of articular cartilage, there is a limited amount of literature regarding the effects of inflammation on the neighboring soft tissue, such as the ACL. Previously, Otani et al found that elderly patients undergoing total knee arthroplasty for long-term osteoarthritis had degenerative changes in their meniscus that were associated with inflammatory cytokine (IL-6 and IL-8) levels [ 7 ]. It is important to understand these changes because damage to the soft tissue architecture secondary to posttraumatic inflammation may subtly impair movement mechanics, place the patient at greater risk of additional ligamentous injury, and portend further PTOA progression [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%